NON-STATIONARY ELECTROMAGNETICS : an integral equations approach. - Nerukh, Alexander ([Place of publication not identified], PAN STANFORD Publishing, 2018)
This book is devoted to the investigations of non-stationary electromagnetic processes. The investigations are undertaken analytically mainly using the Volterra integral equations approach. The book contains a systematic statement of this approach for the investigations of electrodynamics phenomena in the time domain and new results and applications in microwave techniques and photonics. Particular consideration is given to electromagnetic transients in time-varying media and their potential applications. The approach is formulated and electromagnetic phenomena are investigated in detail for a hollow metal waveguide, which contains moving dielectric or plasma-bounded medium, and dielectric waveguides with time-varying medium inside a core.
OCLC-licensed vendor bibliographic record.
Keywords: Electromagnetism; SCIENCE -- Physics -- Electricity; SCIENCE -- Physics -- Electromagnetism; SCIENCE -- Physics; TECHNOLOGY -- Lasers; TECHNOLOGY -- Optics